The American Society of Colon and Rectal Surgeons Clinical Practice Guidelines for the Treatment of Left-Sided Colonic Diverticulitis. Issue 6 (June 2020) - Hall, Jason; Hardiman, Karin; Lee, Sang; Lightner, Amy; Stocchi, Luca; Paquette, Ian M.; Steele, Scott R.; Feingold, Daniel L.
Abstract : Supplemental Digital Content is available in the text.